Thinking and Reasoning : an Introduction to the Psychology of Reason, Judgment and Decision Making. - Manktelow, Ken (Taylor & amp, 2012)
The area of psychological research reviewed in this book is one that is not only increasing in popularity in college curricula, but is also making an ever larger impact on the world outside the classroom. Drawing upon research originally cited in Ken Manktelow's highly successful publication Reasoning and Thinking, this completely rewritten textbook reflects on the revolutionary changes that have occurred in the field in recent years, stemming from the huge expansion in research output, as well as new methods and explanations, and the appearance of numerous books on the subject aimed at the po.